Factors Causing Cost Overrun in Construction Projects in Central Sulawesi - Andi Rizal; Teguh Hilmansyah; Yusfi Hasanah; Hendra Setiawan; Mohamad Sutrisno; Fiisyatin Rodiah; Muhammad; Irwan; Anang Arya N (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Cost overrun is a major challenge in the construction sector, potentially leading to project delays, increased expenditures, and even project failure. Therefore, identifying the factors that contribute to cost overruns is essential for improving the efficiency and success of construction projects. This study focuses on identifying the key factors causing cost overruns in construction projects. By understanding these factors, effective mitigation strategies can be implemented to reduce the risk of cost overruns. The research will employ a descriptive method to evaluate the relationship between various contributing factors. The descriptive research will involve several stages, including the identification of causal factors, questionnaire design, data collection, data analysis, determination of key factors, and control of these factors.